Reducing prescribing errors in paediatric patients by training prescribers. (29th September 2015) - Eisenhut, M; Sun, B; Skinner, S
Abstract : Aim: Prescribing errors are the most common type of medical error and can result in harm particularly if the patients are young children. Aim of this project was to reduce prescribing errors in junior doctors by an educational intervention. Methods: Junior paediatric doctors were enrolled in a programme of written assessment of prescribing skills on induction to their post. They were given individualised feedback and re-assessment together with supervised prescribing, if major errors were found. At the same time the paediatric Pharmacist led in depth audits, to determine the impact of the testing strategy. The setting was the paediatric wards and neonatal unit of a district general hospital. Results: 16 doctors were tested and received feedback. A total of 110 errors were identified in this test out of which 51 were classified as major including wrong dose and frequency and prescribing medication to a patient with a known allergy. 11/16 had their prescribing supervised and re-assessed because they failed the test. Failure resulted from a serious transcribing error where co-amoxyclav was transcribed in a patient with a documented penicillin allergy. Re-audit of prescribing errors after this intervention revealed a reduction of errors from 47 to 21, and patients affected from 19 to 11 per 100 (p=0.001) emergency admissions compared to an audit before the intervention. Conclusions: An intervention including a comprehensive assessment of prescribing skills with detailed individualised feedback can lead to a reduction of prescribing errors in paediatric trainees.